Pengaruh Motivasi Kerja, Kemampuan Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada My Seafood Bogor - Ramitha, Ranidya; Harini, Sri; Kartini, Tini (Innovative: Journal Of Social Science Research, 2024)
This study aims to analyze the effect of work motivation, work ability and work environment on employee performance at My Seafood Bogor. The methods used in this study are descriptive, quantitative and verificative. The use of samples in the study amounted to 42 employees in the distribution of questionnaires. The questionnaire data were tested through classical validity, reliability and assumption test methods. The analysis technique uses ordinal scales to analyze multiple linear regression, multiple correlation analysis, determination coefficient analysis, hypothesis test. Employee responses to work motivation are high, work ability is good enough, the work environment is good enough and employee performance is high. The results showed that simultaneously and partially work motivation, work ability and work environment had a positive and significant effect on the performance of My Seafood Bogor employees.